Is There an Environmental Kuznets Curve: Empirical Evidence in a Cross-section Country Data - Aleksandar Vasilev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper tests the effect of gross domestic product (GDP) per capita on pollution, measured by carbon dioxide (CO2) emissions per capita. World Bank 1992 study claims that pollution rises with income, but at a slower and slower speed and eventually declines. Using Ordinary Least Squares estimation procedure, we find a quadratic relationship ("inverted U-hypothesis") between CO2 emissions per capita and GDP per capita in a cross-section of world countries with data from 2000, thus proving the existence of Environmental Kuznets Curve. The result is important because it may have important policy implications.
Keywords: Q2; 330; Environmental Kuznets curve; pollution